Closing knowledge-action gaps in adaptation to climate change in the Asia-Pacific region - Louis Lebel (2018)
Major knowledge-action gaps remain with respect to adaptation to climate change in the Asia-Pacific. Knowledge-action gaps arise because knowledge is missing, inaccessible or unused. In this study initiatives to close knowledge-action gaps in developing and low-to-middle income countries of the Asia-Pacific region were reviewed. Specific attention was given to: who is involved in the design and implementation; the procedures and roles assigned to different actors; the presence of networks; and, efforts at coordination. Past initiatives to close gaps included promoting communication and education activities, convening reviews and assessments, funding research programmes, establishing coordination offices and supporting pilot community-based actions. Recurrent challenges were observed and related to the specific characteristics of climate change that make the communication and identification of strong incentives difficult and constraints in resources and capacities to carry out research and govern effectively. Four strategies for improving performance were identified. © 2014 Inderscience Enterprises Ltd.